O comportamento no processo de busca da informação por meio das tecnologias da informação e comunicação: um estudo de caso sobre os discentes da Faculdade de Biblioteconomia no Estado do Pará - COSTA, Elisangela Silva da (Universidade Federal do Pará, 2017)
It approaches the relationship between the behavior during the process of information seeking and Information Technology and Communication ( ICT ) , treated in an interdisciplinary perspective in the context of undergraduate Librarianship at the Federal University of Pará ( UFPA ) . This study aims to investigate how undergraduate students in Library hold their academic research by examining whether there is successful the results, focusing , in particular , access to academic texts , for reading and textual production of these students , who are in process vocational training . The methodology was as follows: the first with the literature , based on authors such as Kuhlthau ( 1991 , 1999 , 2004 and 2005 ) , Wilson ( 1997 , 1999 , 2000 and 2006 ) and covering contributions of other thinkers on the subject addressed . In the second step , we performed an exploratory and descriptive study of qualitative and quantitative approach with a questionnaire containing closed, open and hybrid questions . The results show that students generally have satisfactory performance in the information seeking process , therefore, perform the process of information retrieval in a proficient manner.